Effect of the rate of inclusion of field pea in the concentrate of lambs on in vitro fermentation parameters - Lobón M.S.; Joy M.; Rufino-Moya P.J.; Blanco M. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The replacement of soya by local protein sources, as the field pea (Pisum sativum), has been encouraged to reduce the dependency of Europe on soya imports. The aim of this study was to investigate the effect of increasing amounts of field pea in the lamb’s concentrate (0%Pea, 10%Pea, 20%Pea and 30%Pea) on in vitro fermentation. Gas production was determined with the Ankom system for 24 hours and the parameters of kinetics of fermentation were estimated. Methane, ammonia (NH3-N) and in vitro organic matter degradability (IVOMD) were determined. Most of the parameters were affected by the rate of inclusion of pea. The 10%Pea concentrate had the lowest gas production and the NH3-N content (P<0.05). Methane production was lower in 10%Pea than in 30%Pea (P<0.05), presenting 0%Pea and 20%Pea intermediate values. Regarding the IVOMD, the 10%Pea had greater degradability than 20%Pea and 30%Pea (P<0.05) presenting 0%Pea intermediate value (P>0.05). In conclusion, a partial substitution of soya by 10% field pea in lamb’s concentrate could be recommended because it reduced gas and methane production and NH3-N content whereas it increased IVOMD.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)